Statistical Evaluation of Uniform Temperature and Thermal Gradients for Composite Girder of Tibet Region Using Meteorological Data - Yujuan Liu; Zhiyuan Ma; Jiang Liu (Buildings)
To accurately assess the temperature action and effect of steel-concrete composite girder bridges in plateau and cold areas, this paper investigated nearly 50 years of historical meteorological data from 26 meteorological observation stations in the Tibet region of China. Based on the most unfavorable extreme meteorological data at each meteorological station, a finite element model was used to analyze the temperature field of the composite girder. The most unfavorable values of temperature were obtained. The regional differences in temperature actions at different meteorological stations were analyzed, and the isotherm maps of the extreme values of the uniform temperature and thermal gradients were further obtained based on spatial interpolation methods in the ArcGIS program. The study shows that the uniform temperature is significantly affected by the climatic environment, and the isotherm maps provide a visual representation of the geographic distribution pattern of temperature extremes. The maximum and minimum uniform temperatures in Tibet range from 18.28 °C to 42.27 °C and from −41.07 °C to 4.71 °C respectively. The maximum regional difference of positive and negative thermal gradient reaches 11.32 °C and 7.69 °C respectively. The temperature effects calculated using the most unfavorable values of the isotherm map are all more unfavorable than the specification calculations. In particular, the tensile stress of the concrete under the positive thermal gradient reaches 2.91 MPa, which exceeds the standard value of the tensile strength of concrete. This is a significant risk factor for cracking. The compressive stress of the steel girder under a negative thermal gradient reaches 19.35 MPa, which represents a 136% increase compared to the specified value. This increase elevates the risk of instability in the steel girder.